Multiple Parafoveal Holes after Pars Plana Vitrectomy for Retinal Detachment Surgery - Paliwal, Sonal; Upadhyay, Prerna; Patel, Samta (Nepalese Journal of Ophthalmology, 2025)
Introduction: To report a case of secondary multiple parafoveal holes after internal limiting membrane (ILM) peeling in case of a vitrectomy surgery for rhegmatogenous retinal detachment. Case: Thirty-two years old male myopic patient presented with total rhegmatogenous retinal detachment with vision of counting fingers with proliferative vitreoretinopathy (PVR) grade B. He underwent right eye Belt buckle with uncomplicated pars plana vitrectomy with ILM peeling with silicon oil insertion. Observation: On routine follow up, multiple eccentric parafoveal retinal holes were noticed after two months of pars plana vitrectomy (PPV) which remained stable six months post silicon oil removal with visual acuity (VA) 20/80. Conclusion: Parafoveal retinal holes may develop due to mechanical surgical trauma leading to retinal weakening caused by muller cell damage followed by a hole formation.